Réponses

2012-04-26T21:32:08+02:00
Meilleure réponse !
2012-04-26T21:51:50+02:00

A = (-7x +5)(-7x + 5) + ( -7x +5)(x-7)=0

   = (-7x + 5)(-7x + 5 +x - 7)=0

  = (-7x + 5)(-6x -2)=0

donc il y a deux solutions: 

-7x +5 =0      5 = 7x           x = 5/7 = 0,7

et -6x -2 =0           -6x = 2      x = -3

 

B= (2x+4)²-(2x+4)(-x+12)=0

  = (2x+4)(2x+4)-(2x+4)(-x+12)=0

  = (2x+4)[2x+4 -(x+12)]

 = (2x + 4)(2x + 4 +x -12)

 = (2x + 4)(3x - 8)

donc deux solutions :

2x + 4 =0     2x = -4      x = -2

et  3x-8 =0    3x = 8     x = 8/3 = 2,6


C = (-7x+11)²=36

   = (-7x + 11)² = 6²

  = (-7x + 11)² -6² =0

  = (-7x +11 +6)(-7x+11-6) =0

  = (-7x +17)(-7x + 5 ) =0

donc deux solutions :

-7x + 17 = 0      17=7x      x = 17/7 = 2,4

et   -7x+5 = 0          5 = 7x   x=5/7 = 0,7



voilà, je crois que c'est ça